Copper-Promoted Hiyama Cross-Coupling of Arylsilanes With Thiuram Reagents: A Facile Synthesis of Aryl Dithiocarbamates - Wang, Yiying; Shen, Hongtao; Qiu, Jianhua; Chen, Mengqi; Song, Weimin; Zhao, Mingqin; Wang, Longfei; Bai, Feng; Wang, Hongxia; Wu, Zhiyong (Frontiers in Chemistry, 2022)
We report herein a facile Hiyama cross-coupling reaction of arylsilanes with thiuram reagents (tetraalkylthiuram disulfides or tetraalkylthiuram monosulfide) enabled by copper fluoride. Compared to our previous work, this protocol is an alternative protocol for the generation of S-aryl dithiocarbamates. It features low toxic and readily available substrates, cost-effective promoter, easy performance, and provides good yields.